Waterproof anti-cracking formaldehyde-free multilayer composite board and manufacturing process thereof
By adopting the design and specific process steps of the five-layer structure in the composite panel, the shortcomings of existing UV light curing coatings in terms of water resistance and mechanical properties are solved, and the water resistance and crack resistance of the composite panels are improved, and the safety and environmental protection of the products are ensured.
Patent Information
- Application Number
- CN202311366223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
Existing UV photocuring coatings have shortcomings in water resistance and mechanical properties, and composite wood panels are prone to seepage and cracking when temperature difference changes.
The water-resistant and crack-proof composite board with a five-layer structure, including log slices, adhesive layer, finish paper and surface paint layer, improves the water-resistant and crack-proof performance of the composite board through specific process steps and material combinations.
The water resistance and crack resistance of composite boards are improved, the adhesion, hardness and mechanical properties of the surface paint layer are enhanced, and the use of formaldehyde is avoided, ensuring the safety and environmental protection of the product.
Smart Images

Figure BDA0004504412450000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite boards, in particular to a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board and a manufacturing process thereof. Background Art
[0002] With the continuous development of the coating industry, people's concept of energy saving, environmental protection and health has deepened. Due to its "5E" advantages of high efficiency, environmental protection, energy saving, economy and wide adaptability, UV light-curing coatings have developed rapidly. UV light-curing coatings use the energy of ultraviolet light to excite photoinitiators, triggering polymerization and cross-linking reactions between the photosensitive resin in the coating and the monomer molecules as active diluents, thereby hardening the paint film. It is a chemical drying achieved by forming chemical bonds. UV light-curing coatings have the advantages of low organic matter (Voc) emissions, fast curing speed, and can be applied to heat-sensitive substrates (plastics, paper, wood) and other advantages and have developed rapidly and been widely used. Among the existing UV light-curing coatings, polyurethane coatings have many applications, and their water resistance is poor; and UV light-curing coatings often add diluents, which will shrink greatly after light curing, affecting the hardness and mechanical properties of the paint film. In addition, in the application of composite wood boards, due to the influence of indoor and outdoor temperature differences and dry and cold weather, the moisture content of the wood will change greatly, disrupting the fiber structure inside the wood, affecting the stability of the product, and causing water seepage and cracking of wooden furniture finishes. Therefore, we propose a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board and a manufacturing process thereof. Summary of the invention
[0003] The object of the present invention is to provide a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board and a manufacturing process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a water-resistant, crack-proof, formaldehyde-free multi-layer composite board, comprising log slices, an adhesive layer, facing paper and a surface paint layer;
[0005] The number of layers of the log slices is five, the facing paper is located on the upper surface of the uppermost log slice, and the surface paint layer is arranged on the upper surface of the facing paper;
[0006] The facing paper, the top layer of log slices and two adjacent layers of log slices are bonded together by adhesive to form an adhesive layer.
[0007] Furthermore, the thickness of the composite board is 18 to 22 mm.
[0008] Furthermore, the log slices are Australian pine boards, and the thickness of a layer of log slices is 3.5 to 5.5 mm.
[0009] Furthermore, the adhesive layer is made of Huntsman MDI adhesive with a thickness of 0.03 to 0.05 mm.
[0010] Furthermore, the facing paper is from Schattdecor of Germany, with a specification of 100-120g / ㎡.
[0011] Furthermore, the surface paint layer is formed by UV curing of the surface paint and has a thickness of 0.05 to 0.10 mm.
[0012] In the above technical solution, the log slices are placed in a ventilated and cool place for three months to dry before use, which can effectively prevent the deformation and cracking of the wood and enhance the comprehensive performance of the composite board.
[0013] A process for producing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0014] Take five layers of log slices, apply adhesive on the upper surface, overlap them, and form a composite board; lay facing paper on the upper surface of the composite board, and press it;
[0015] The surface paint is applied to the surface of the facing paper and UV-cured to form a surface paint layer to obtain a composite board.
[0016] Furthermore, the pressing process is 0.03-0.05MPa.
[0017] Furthermore, the surface paint is obtained by mixing branched modified polyurethane, modified polysulfide, photoinitiator and auxiliary agent.
[0018] Furthermore, the surface paint comprises the following components by mass: 20 to 60 parts of branched modified polyurethane, 10 to 30 parts of modified polysulfide, 2 to 3 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine.
[0019] Furthermore, the branched modified polyurethane is prepared by the following process:
[0020] The polyhydroxy compound and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25-30°C for 12 hours under the protection of a nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, the temperature is raised to 70-80°C and the mixture is reacted for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain a branched modified polyurethane.
[0021] Furthermore, the ratio of the polyhydroxy compound to N,N-dimethylformamide is 10 g / 100 mL.
[0022] Furthermore, the branched modified polyurethane includes the following components by mass: 100 to 116 parts of polyhydroxy compounds, 55 to 60 parts of isophorone diisocyanate, 0.2 to 0.3 parts of dibutyltin dilaurate, 32.7 to 34.8 parts of hydroxyethyl acrylate, 40.7 to 42.2 parts of hydroxyethyl methacrylate, and 0.4 to 0.5 parts of p-hydroxyanisole.
[0023] Further, the polyol is prepared by the following process:
[0024] Mix cyanuric chloride, acetone and deionized water, stir and adjust the system temperature to 0-5°C, slowly add piperazine and sodium hydroxide solution, add within 2 hours, and react for 100-150 minutes; heat to 35-40°C, add diethanolamine, and react for 100-150 minutes; evaporate acetone, add aminobenzenethiol and sodium hydroxide solution, and continue to react for 6-8 hours; vacuum filter, wash with acetone, wash with water, and dry to constant weight to obtain a polyhydroxy compound.
[0025] Further, the polyol comprises the following components by mass: 18.4 parts of cyanuric chloride, 4.3-4.4 parts of piperazine, 5.3-5.4 parts of diethanolamine, and 6.2-6.4 parts of aminobenzenethiol;
[0026] The ratio of cyanuric chloride, acetone and deionized water is 37g:175mL:70mL;
[0027] The concentration of sodium hydroxide solution is 0.2M;
[0028] Before use, aminobenzenethiol was protected by 1-nitro-2,4-dibenzylthiol.
[0029] Further, the modified polysulfide is prepared by the following process:
[0030] The trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide are mixed, and under the protection of nitrogen atmosphere, 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, glycidyl methacrylate and a catalyst are added, and the mixture is reacted at a temperature of 30 to 35°C for 5 to 6 hours; the mixture is concentrated, precipitated and dried to obtain a modified polysulfide.
[0031] Further, the ratio of trimethylolpropane tris(3-mercaptopropionate) to N,N-dimethylformamide is 25 g / 100 mL;
[0032] The modified polysulfide comprises the following components by weight: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 1.6-3.2 parts of 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, 1.4-3.0 parts of glycidyl methacrylate, and 0.03-0.04 parts of a catalyst;
[0033] The catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU).
[0034] Furthermore, the process conditions of UV curing are: high-pressure UV light irradiation for 15 to 45 seconds and a wavelength of 300 to 400 nm.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] In the above technical scheme, in an acetone and deionized water system, sodium hydroxide is used as an acid binding agent to react and condense the chlorine in cyanuric chloride with the amino groups in piperazine, diethanolamine and aminobenzenethiol to obtain a polyhydroxy compound with a triazine structure as a core to form a branched structure; the triazine structure is used as a polyol to react with diisocyanate, and hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added to prepare a polyurethane acrylate having a double bond and a thiol group (protecting group), which is recorded as a branched modified polyurethane. The introduction of triazine and piperazine structures can effectively improve the adhesion, stability and water resistance and heat resistance of the surface paint layer, and as a rigid skeleton, the mechanical properties of the surface paint layer are improved at the same time.
[0037] In a dry nitrogen and N,N-dimethylformamide solvent system, the catalyst causes the mercapto group in trimethylolpropane tris(3-mercaptopropionate) to react with the double bonds in 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate and glycidyl methacrylate to obtain a thioether, which can improve the toughness of the prepared surface paint layer and form a branched structure, recorded as a modified polythioether, which has an epoxy-terminated structure and is convenient for subsequent UV curing of the surface paint; the introduction of fluorine element can improve the hardness and water resistance of the prepared surface paint layer.
[0038] Branched modified polyurethane and modified polysulfide are mixed as the resin material of the surface paint. Both are branched molecules with reduced entanglement between molecular chains and a large number of active terminal functional groups, which reduces the viscosity of the surface paint, reduces the use of diluents, reduces toxicity, avoids a decrease in curing rate, an increase in the shrinkage of the surface paint layer, and a decrease in adhesion, hardness, water resistance, tensile strength, impact resistance and other properties.
[0039] The thiol protective agent in the branched modified polyurethane leaves under UV light, exposing the thiol group; under the action of the photoinitiator and the auxiliary agent, it reacts and cross-links with the double bonds and the epoxy groups in the modified polysulfide to form a three-dimensional network cross-linking structure, and the number of double bonds is reduced, which can effectively improve the toughness of the surface paint layer and improve its adhesion; the sufficient content of photosensitive groups helps to improve the hardness of the surface paint layer; the internal cavity formed by the three-dimensional cross-linking structure can effectively reduce the internal stress of the surface paint layer, reduce its curing shrinkage, and further improve the comprehensive properties of the surface paint layer such as hardness, tensile strength, and impact resistance, so as to achieve water resistance and crack resistance of the composite board; and no formaldehyde is added in the material system of the composite board, which is safer and more environmentally friendly. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the following specific implementations,
[0042] The log slices are Australian pine boards, with a thickness of 4.0mm per layer. They are placed in a ventilated and cool place to dry for three months before use. The adhesive layer uses Huntsman MDI glue, with a single layer coating thickness of 0.05mm. The facing paper comes from Schattdecor of Germany, with a specification of 100g / ㎡.
[0043] Thiol protection process of aminobenzenethiol:
[0044] Mix 0.10 mol 1-nitro-2,4-dibenzyl mercaptan, 35 mL deionized water, and 65 mL ethanol, add 0.12 mol thiourea, 5 mL 36% concentrated hydrochloric acid, and 5 mL 30% hydrogen peroxide at 2°C, and react for 5 hours; add 0.01 mol aminobenzenethiol and react for 8 hours; extract, concentrate under reduced pressure, and dry;
[0045] The following “parts” are all parts by mass.
[0046] Embodiment 1: A process for manufacturing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0047] Step (1) preparing the surface paint:
[0048] 1.1. Preparation of polyols:
[0049] Mix cyanuric chloride, acetone and deionized water, stir and adjust the system temperature to 0°C, slowly add piperazine and sodium hydroxide solution, add within 2 hours, and react for 150 minutes; heat to 35°C, add diethanolamine, and react for 150 minutes; evaporate acetone, add aminobenzenethiol and sodium hydroxide solution, and continue to react for 6 hours; vacuum filter, wash with acetone, wash with water, and dry to constant weight to obtain a polyhydroxy compound; the polyhydroxy compound includes the following mass components: 18.4 parts of cyanuric chloride, 4.3 parts of piperazine, 5.3 parts of diethanolamine, and 6.4 parts of aminobenzenethiol; the ratio of cyanuric chloride, acetone and deionized water is 37g:175mL:70mL; the concentration of the sodium hydroxide solution is 0.2M;
[0050] 1.2. Preparation of branched modified polyurethane:
[0051] The polyol and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 70°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of the polyol and N,N-dimethylformamide is 10 g / 100 mL; the branched modified polyurethane comprises the following mass components: 100 parts of the polyol, 55 parts of isophorone diisocyanate, 0.2 parts of dibutyltin dilaurate, 32.7 parts of hydroxyethyl acrylate, 40.7 parts of hydroxyethyl methacrylate and 0.4 parts of p-hydroxyanisole;
[0052] 1.3. Preparation of modified polysulfide:
[0053] Trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide are mixed, and under the protection of nitrogen atmosphere, 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, glycidyl methacrylate and a catalyst are added, and the mixture is reacted at 30°C for 5 hours; the mixture is concentrated, precipitated and dried to obtain a modified polysulfide; the ratio of trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide is 25 g / 100 mL; the modified polysulfide comprises the following components by mass: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 1.6 parts of 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, 1.4 parts of glycidyl methacrylate and 0.03 parts of a catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);
[0054] 1.4. Preparation of surface paint:
[0055] 60 parts of branched modified polyurethane, 10 parts of modified polysulfide, 2 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine are mixed to obtain a surface paint;
[0056] Step (2) Preparation of composite board:
[0057] Take five layers of log slices, apply adhesive on the upper surface, overlap them to form a composite board; lay facing paper on the upper surface of the composite board, and press at 0.03MPa for 60s;
[0058] The surface paint is applied to the surface of the facing paper with a coating thickness of 0.05 mm and UV cured under the following process conditions: high-pressure UV light irradiation for 15 seconds with a wavelength of 365 nm to form a surface paint layer and obtain a composite board.
[0059] Embodiment 2: A process for manufacturing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0060] Step (1) preparing the surface paint:
[0061] 1.1. Preparation of polyols:
[0062] Mix cyanuric chloride, acetone and deionized water, stir and adjust the system temperature to 2°C, slowly add piperazine and sodium hydroxide solution, add within 2 hours, and react for 120 minutes; heat to 37°C, add diethanolamine, and react for 120 minutes; evaporate acetone, add aminobenzenethiol and sodium hydroxide solution, and continue to react for 7 hours; vacuum filter, wash with acetone, wash with water, and dry to constant weight to obtain a polyhydroxy compound; the polyhydroxy compound includes the following mass components: 18.4 parts of cyanuric chloride, 4.35 parts of piperazine, 5.35 parts of diethanolamine, and 6.3 parts of aminobenzenethiol; the ratio of cyanuric chloride, acetone and deionized water is 37g:175mL:70mL; the concentration of the sodium hydroxide solution is 0.2M;
[0063] 1.2. Preparation of branched modified polyurethane:
[0064] The polyol and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 27°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 75°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of the polyol and N,N-dimethylformamide is 10 g / 100 mL; the branched modified polyurethane comprises the following components by mass: 108 parts of the polyol, 57 parts of isophorone diisocyanate, 0.25 parts of dibutyltin dilaurate, 33.7 parts of hydroxyethyl acrylate, 41.5 parts of hydroxyethyl methacrylate and 0.45 parts of p-hydroxyanisole;
[0065] 1.3. Preparation of modified polysulfide:
[0066] The mixture of trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide was mixed, and 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, glycidyl methacrylate and a catalyst were added under the protection of a nitrogen atmosphere, and the mixture was reacted at 32°C for 5.5 hours; the mixture was concentrated, precipitated and dried to obtain a modified polysulfide; the ratio of trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide was 25 g / 100 mL; the modified polysulfide included the following components by mass: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 2.4 parts of 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, 2.2 parts of glycidyl methacrylate and 0.035 parts of a catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);
[0067] 1.4. Preparation of surface paint:
[0068] 60 parts of branched modified polyurethane, 20 parts of modified polysulfide, 2.5 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine were mixed to obtain a surface paint;
[0069] Step (2) Preparation of composite board:
[0070] Take five layers of log slices, apply adhesive on the upper surface, overlap them, and form a composite board; lay facing paper on the upper surface of the composite board, and press at 0.04MPa for 60s;
[0071] The surface paint is applied to the surface of the facing paper with a coating thickness of 0.08 mm and UV curing. The process conditions are: high-pressure UV light irradiation for 30 seconds with a wavelength of 365 nm to form a surface paint layer to obtain a composite board.
[0072] Embodiment 3: A process for manufacturing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0073] Step (1) preparing the surface paint:
[0074] 1.1. Preparation of polyols:
[0075] Mix cyanuric chloride, acetone and deionized water, stir and adjust the system temperature to 5°C, slowly add piperazine and sodium hydroxide solution, add within 2 hours, and react for 150 minutes; heat to 40°C, add diethanolamine, and react for 100 minutes; evaporate acetone, add aminobenzenethiol and sodium hydroxide solution, and continue to react for 8 hours; vacuum filter, wash with acetone, wash with water, and dry to constant weight to obtain a polyhydroxy compound; the polyhydroxy compound includes the following mass components: 18.4 parts of cyanuric chloride, 4.4 parts of piperazine, 5.4 parts of diethanolamine, and 6.4 parts of aminobenzenethiol; the ratio of cyanuric chloride, acetone and deionized water is 37g:175mL:70mL; the concentration of the sodium hydroxide solution is 0.2M;
[0076] 1.2. Preparation of branched modified polyurethane:
[0077] The polyol and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 30°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 80°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of the polyol and N,N-dimethylformamide is 10 g / 100 mL; the branched modified polyurethane comprises the following mass components: 116 parts of the polyol, 60 parts of isophorone diisocyanate, 0.3 parts of dibutyltin dilaurate, 34.8 parts of hydroxyethyl acrylate, 42.2 parts of hydroxyethyl methacrylate and 0.5 parts of p-hydroxyanisole;
[0078] 1.3. Preparation of modified polysulfide:
[0079] The trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide are mixed, and under the protection of nitrogen atmosphere, 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, glycidyl methacrylate and a catalyst are added, and the mixture is reacted at 35°C for 6 hours; the mixture is concentrated, precipitated and dried to obtain a modified polysulfide; the ratio of trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide is 25 g / 100 mL; the modified polysulfide comprises the following components by mass: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 3.2 parts of 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, 3.0 parts of glycidyl methacrylate and 0.04 parts of a catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);
[0080] 1.4. Preparation of surface paint:
[0081] 60 parts of branched modified polyurethane, 30 parts of modified polysulfide, 3 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine were mixed to obtain a surface paint;
[0082] Step (2) Preparation of composite board:
[0083] Take five layers of log slices, apply adhesive on the upper surface, overlap them, and form a composite board; lay facing paper on the upper surface of the composite board, and press at 0.05MPa for 60s;
[0084] The surface paint is applied to the surface of the facing paper with a coating thickness of 0.10 mm and UV curing. The process conditions are: high-pressure UV light irradiation for 45 seconds with a wavelength of 365 nm to form a surface paint layer to obtain a composite board.
[0085] Comparative Example 1: A process for producing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0086] Step (1) preparing the surface paint:
[0087] 1.1. Take pentaerythritol triacrylate as the polyol:
[0088] 1.2. Preparation of branched modified polyurethane:
[0089] The polyol and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 70°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of the polyol and N,N-dimethylformamide is 10 g / 100 mL; the branched modified polyurethane comprises the following components by mass: 16 parts of the polyol, 55 parts of isophorone diisocyanate, 0.2 parts of dibutyltin dilaurate, 32.7 parts of hydroxyethyl acrylate, 40.7 parts of hydroxyethyl methacrylate and 0.4 parts of p-hydroxyanisole;
[0090] Steps 1.3-1.4 and (2) are the same as those in Example 1 to obtain a composite board.
[0091] Comparative Example 2: A process for producing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0092] Step (1) preparing the surface paint:
[0093] 1.1. Preparation of branched modified polyurethane:
[0094] Pentaerythritol triacrylate and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 70°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of pentaerythritol triacrylate to N,N-dimethylformamide is 10g / 100mL; the branched modified polyurethane comprises the following mass components: 16 parts of pentaerythritol triacrylate, 55 parts of isophorone diisocyanate, 0.2 parts of dibutyltin dilaurate, 32.7 parts of hydroxyethyl acrylate, 40.7 parts of hydroxyethyl methacrylate and 0.4 parts of p-hydroxyanisole;
[0095] 1.2. Preparation of modified polysulfide:
[0096] Trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide are mixed, and glycidyl methacrylate and a catalyst are added under the protection of a nitrogen atmosphere, and the mixture is reacted at 30°C for 5 hours; the mixture is concentrated, precipitated, and dried to obtain a modified polysulfide; the ratio of trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide is 25 g / 100 mL; the modified polysulfide comprises the following mass components: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 3.0 parts of glycidyl methacrylate, and 0.03 parts of a catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);
[0097] 1.3. Preparation of surface paint:
[0098] 60 parts of branched modified polyurethane, 10 parts of modified polysulfide, 2 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine are mixed to obtain a surface paint;
[0099] Step (2) is the same as in Example 1 to obtain a composite board.
[0100] Comparative Example 3: A process for producing a water-resistant, crack-resistant, formaldehyde-free multilayer composite board, comprising the following process steps:
[0101] Step (1) preparing the surface paint:
[0102] 1.1. Preparation of branched modified polyurethane:
[0103] Pentaerythritol triacrylate and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25°C for 12 hours under the protection of nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, and the mixture is heated to 70°C for 4 hours; the mixture is concentrated, precipitated in anhydrous ether, rotary evaporated and vacuum dried to obtain branched modified polyurethane; the ratio of pentaerythritol triacrylate to N,N-dimethylformamide is 10g / 100mL; the branched modified polyurethane comprises the following mass components: 16 parts of pentaerythritol triacrylate, 55 parts of isophorone diisocyanate, 0.2 parts of dibutyltin dilaurate, 32.7 parts of hydroxyethyl acrylate, 40.7 parts of hydroxyethyl methacrylate and 0.4 parts of p-hydroxyanisole;
[0104] 1.2. Preparation of surface paint:
[0105] 60 parts of branched modified polyurethane, 2 parts of trimethylolpropane tris(3-mercaptopropionate), 2 parts of photoinitiator benzophenone (PB), and 1 part of auxiliary agent triethylamine were mixed to obtain a surface paint;
[0106] Step (2) is the same as in Example 1 to obtain a composite board.
[0107] Experiment: Take the composite boards obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, test their properties respectively and record the test results:
[0108] Hardness test: GB / T 6739 is used as the reference standard, and a pencil hardness tester is used to test the pencil hardness of the surface paint layer of the composite board;
[0109] Adhesion test: GB / T9286 is used as the reference standard, and a paint film adhesion tester is used to test the adhesion of the surface paint layer of the composite board;
[0110] Impact strength test: GB / T 1732 is used as the reference standard, and an impact tester is used to test the impact strength of the surface paint layer in the composite board.
[0111] Tensile strength test: Use a tensile testing machine to test the tensile strength of the surface paint layer in the composite board, the tensile rate is 5mm / min, and the test temperature is 25℃;
[0112] Water resistance test: A video optical contact angle measuring instrument is used to detect the water contact angle of the surface paint layer in the composite board for testing.
[0113]
[0114] According to the data in the above table, we can clearly draw the following conclusions:
[0115] The composite plates obtained in Examples 1-3 are compared with the composite plates obtained in Comparative Examples 1-3. The test results show that:
[0116] Compared with the comparative example, the composite panels obtained in Examples 1-3 have surface paint layers with higher hardness, adhesion grade, tensile strength, impact strength and contact angle data, which fully demonstrates that the invention achieves improvements in the hardness, adhesion, mechanical properties and water resistance of the surface paint layer of the composite panels, and improves the water resistance and crack resistance of the composite panels.
[0117] Compared with Example 1, pentaerythritol triacrylate is used as the polyhydroxy compound in Comparative Example 1; on the basis of Comparative Example 1, the preparation components of the modified polysulfide in Comparative Example 2 are different; on the basis of Comparative Example 1, trimethylolpropane tris(3-mercaptopropionate) is used to replace the modified polysulfide in Comparative Example 3; the composite boards obtained in Comparative Examples 1-3 have a surface paint layer with higher hardness, adhesion grade, tensile strength, impact strength and decreased contact angle data. It can be seen that the setting of the surface paint components and the preparation process thereof in the present invention can promote the improvement of the hardness, adhesion performance, mechanical properties and water resistance of the surface paint layer, and help to improve the water resistance and crack resistance of the composite board.
[0118] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0119] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board, characterized in that: The process steps include: Take five layers of log slices, apply adhesive on the upper surface, overlap them, and form a composite board; lay facing paper on the upper surface of the composite board, and press it; Applying a surface paint on the surface of the facing paper and UV curing to form a surface paint layer to obtain a composite board; The surface paint comprises the following components by mass: 20 to 60 parts of branched modified polyurethane, 10 to 30 parts of modified polythioether, 2 to 3 parts of photoinitiator and 1 part of auxiliary agent.
2. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 1, characterized in that: The branched modified polyurethane is prepared by the following process: The polyhydroxy compound and N,N-dimethylformamide are mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 25-30°C for 12 hours under the protection of a nitrogen atmosphere; hydroxyethyl acrylate, hydroxyethyl methacrylate and p-hydroxyanisole are added, the temperature is raised to 70-80°C and the mixture is reacted for 4 hours to obtain a branched modified polyurethane.
3. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 2, characterized in that: The polyol is prepared by the following process: Mix cyanuric chloride, acetone and deionized water, stir and adjust the system temperature to 0-5°C, slowly add piperazine and sodium hydroxide solution within 2 hours, and react for 100-150 minutes; heat to 35-40°C, add diethanolamine, and react for 100-150 minutes; evaporate acetone, add aminobenzenethiol and sodium hydroxide solution, and continue to react for 6-8 hours to obtain a polyhydroxy compound.
4. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 1, characterized in that: The modified polysulfide is prepared by the following process: Trimethylolpropane tris(3-mercaptopropionate) and N,N-dimethylformamide are mixed, and under the protection of nitrogen atmosphere, 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, glycidyl methacrylate and a catalyst are added, and the mixture is reacted at a temperature of 30 to 35° C. for 5 to 6 hours to obtain a modified polysulfide.
5. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 2, characterized in that: The branched modified polyurethane comprises the following components by mass: 100-116 parts of polyhydroxy compounds, 55-60 parts of isophorone diisocyanate, 0.2-0.3 parts of dibutyltin dilaurate, 32.7-34.8 parts of hydroxyethyl acrylate, 40.7-42.2 parts of hydroxyethyl methacrylate, and 0.4-0.5 parts of p-hydroxyanisole.
6. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 3, characterized in that: The polyhydroxy compound comprises the following components by weight: 18.4 parts of cyanuric chloride, 4.3-4.4 parts of piperazine, 5.3-5.4 parts of diethanolamine, and 6.2-6.4 parts of aminobenzenethiol.
7. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 4, characterized in that: The modified polythioether comprises the following components by weight: 4.0 parts of trimethylolpropane tris(3-mercaptopropionate), 1.6-3.2 parts of 2,2,3,3,3-pentafluoro-2-fluoropropyl acrylate, 1.4-3.0 parts of glycidyl methacrylate, and 0.03-0.04 parts of a catalyst.
8. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 1, characterized in that: The process conditions of UV curing are: high-pressure UV light irradiation for 15 to 45 seconds and a wavelength of 300 to 400 nm.
9. The process for producing a water-resistant, crack-resistant, formaldehyde-free multi-layer composite board according to claim 1, characterized in that: The thickness of the composite board is 18 to 22 mm.
10. A water-resistant, crack-resistant, formaldehyde-free multi-layer composite board made according to the manufacturing process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Laminate and method for producing same
CA2897484A1
Water-based paint resin film veneer solid wood composite floor with low VOCs release and preparation method thereof
CN112455028A
Method of making a veneer with a highly glossy coating
EP0699545A2
Composite structure with a polyurethane coating, method for its manufacture and application
EP1927466A1
Laminate including polymeric body adhesively bonded to irradiated coating of paint
US4321307A